Perturbative approach for diffraction due to a periodically corrugated boundary between vacuum and a negative phase-velocity material - Depine, Ricardo Angel (2004)
Using a perturbative approach, we study the changes that the transformation of a refracting medium from positive/negative phase velocity to negative/positive phase velocity has on the diffraction of a plane wave due to a periodically corrugated boundary. In contrast to specular reflection, we find that nonspecular reflection, albeit weak for weakly corrugated boundaries, is highly affected by the type of refracting medium, due to the involvement of evanescent waves in the troughs of the corrugated boundary. © 2004 Elsevier B.V. All rights reserved.